Bidirectional Action of Cenicriviroc, a CCR2/CCR5 Antagonist, Results in Alleviation of Pain-Related Behaviors and Potentiation of Opioid Analgesia in Rats With Peripheral Neuropathy - Kwiatkowski, Klaudia; Pawlik, Katarzyna; Ciapała, Katarzyna; Piotrowska, Anna; Makuch, Wioletta; Mika, Joanna (Frontiers in Immunology, 2020)
Clinical management of neuropathic pain is unsatisfactory, mainly due to its resistance to the effects of available analgesics, including opioids. Converging evidence indicates the functional interactions between chemokine and opioid receptors and their influence on nociceptive processes. Recent studies highlight that the CC chemokine receptors type 2 (CCR2) and 5 (CCR5) seem to be of particular interest. Therefore, in this study, we investigated the effects of the dual CCR2/CCR5 antagonist, cenicriviroc, on pain-related behaviors, neuroimmune processes, and the efficacy of opioids in rats after chronic constriction injury (CCI) of the sciatic nerve. To define the mechanisms of action of cenicriviroc, we studied changes in the activation/influx of glial and immune cells and, simultaneously, the expression level of CCR2, CCR5, and important pronociceptive cytokines in the spinal cord and dorsal root ganglia (DRG). We demonstrated that repeated intrathecal injections of cenicriviroc, in a dose-dependent manner, alleviated hypersensitivity to mechanical and thermal stimuli in rats after sciatic nerve injury, as measured by von Frey and cold plate tests. Behavioral effects were associated with the beneficial impact of cenicriviroc on the activation/influx level of C1q/ IBA-1-positive cells in the spinal cord and/or DRG and GFAP-positive cells in DRG. In parallel, administration of cenicriviroc decreased the expression of CCR2 in the spinal cord and CCR5 in DRG. Concomitantly, we observed that the level of important pronociceptive factors (e.g., IL-1beta, IL-6, IL-18, CCL3) were increased in the lumbar spinal cord and/or DRG 7 days following injury, and cenicriviroc was able to prevent these changes. Additionally, repeated administration of this dual CCR2/CCR5 antagonist enhanced the analgesic effects of morphine and buprenorphine in neuropathic rats, which can be associated with the ability of cenicriviroc to prevent nerve injury-induced downregulation of all opioid receptors at the DRG level. Overall, our results suggest that pharmacological modulation based on the simultaneous blockade of CCR2 and CCR5 may serve as an innovative strategy for the treatment of neuropathic pain, as well as in combination with opioids.